Abnormal hematologic profiles in elite cross-country skiers: Blood doping or? - Stray-Gundersen, J.; Videman, T.; Penttilä, I.; Lereim, I. (Clinical Journal of Sport Medicine, 2003)
Objective: There is widespread public concern about fairness in sports. Blood doping undermines fairness and places athletes' health at risk. The purpose of this study was to examine the prevalence of abnormal hematologic profiles in elite cross-country skiers, which may indicate a high probability of blood doping. Setting and Participants: Samples were obtained as part of routine International Ski Federation blood testing procedures from participants at the World Ski Championships. Sixty-eight percent of all skiers and 92% of those finishing in the top 10 places were tested. Main Outcome Measures: Using flow cytometry, we analyzed erythrocyte and reticulocyte indices. Reference values were from the 1989 Nordic Ski World Championships data set and the International Olympic Committee Erythropoietin 2000 project. Results: Of the skiers tested and finishing within the top 50 places in the competitions, 17% had "highly abnormal" hematologic profiles, 19% had "abnormal" values, and 64% were normal. Fifty percent of medal winners and 33% of those finishing from 4th to 10th place had highly abnormal hematologic profiles. In contrast, only 3% of skiers finishing from 41st to 50th place had highly abnormal values. Conclusions: These data suggest that blood doping is both prevalent and effective in cross-country ski racing, and current testing programs for blood doping are ineffective. It is unlikely that blood doping is less common in other endurance sports. Ramifications of doping affect not only elite athletes who may feel compelled to risk their health but also the general population, particularly young people.